Uplink NOMA-MIMO Systems with Rayleigh Power Distribution - Mikhail Bakulin; Taoufik Ben Rejeb; Vitaly Kreyndelin; Denis Pankratov; Aleksei Smirnov (Sensors, 2022)
The article is devoted to multiple-input multiple-output antenna systems, also called MIMO systems, which are widely used in wireless communication systems. In this article we consider a case when the MIMO system works in overloaded mode. In this mode MIMO systems can be considered as a system with non-orthogonal multiple access NOMA. The main goal of this article is to analyze this interesting case using statistical computer simulation. Based on the analysis of the capacity of a discrete-continuous multiuser MIMO uplink channel, the possibility of such systems functioning in overload mode is proved.